2020
DOI: 10.1002/mus.27124
|View full text |Cite
|
Sign up to set email alerts
|

Utility of neuromuscular ultrasound in the investigation of common mononeuropathies in everyday neurophysiology practice

Abstract: Introduction In everyday clinical neurophysiology practice, mononeuropathies are evaluated primarily by traditional electrodiagnostic testing. We sought to assess the additional benefit of neuromuscular ultrasound (US) in this scenario. Methods All consecutive mononeuropathies undergoing combined US and electrodiagnostic evaluation over a 23‐mo period at a single neurophysiology practice were reviewed. Three independent examiners assessed how often US was: (a) “contributory” ‐ enabling a definite diagnosis not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Our study has confirmed the findings of the earlier studies, 59,60 expands the results further to a larger and more diffuse cohort of neuromuscular disorders beyond mononeuropathies, and reviews how HRUS influences subsequent treatment. HRUS frequently has a decisive role in guiding subsequent management, which then, in some patients, likely influences outcomes.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Our study has confirmed the findings of the earlier studies, 59,60 expands the results further to a larger and more diffuse cohort of neuromuscular disorders beyond mononeuropathies, and reviews how HRUS influences subsequent treatment. HRUS frequently has a decisive role in guiding subsequent management, which then, in some patients, likely influences outcomes.…”
supporting
confidence: 88%
“…Previous work has primarily focused on assessing the value of HRUS in mononeuropathies, especially those secondary to trauma. [58][59][60] In those studies, HRUS improved patient-reported outcomes and changed the diagnostic and therapeutic management in a substantial number of patients, including making a correct diagnosis that could not have been made without HRUS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the overall contribution of NMUS when evaluating focal mononeuropathies. Two showed that the findings nearly always confirmed or contributed new information to EDX 81,91 . One well-designed double-blinded randomized controlled trial comparing outcomes of patients in the EDX laboratory with and without the addition of NMUS showed trends toward improvement in most measures, although most did not reach statistical significance 1 .…”
Section: Specific Conditionsmentioning
confidence: 98%
“…Two showed that the findings nearly always confirmed or contributed new information to EDX. 81,91 One well-designed double-blinded randomized controlled trial comparing outcomes of patients in the EDX laboratory with and without the addition of NMUS showed trends toward improvement in most measures, although most did not reach statistical significance. 1 These multiple converging trends are unlikely because of chance and may have reached statistical significance in a larger trial.…”
Section: General Focal Mononeuropathiesmentioning
confidence: 99%
“…Neuromuscular ultrasound is becoming increasingly helpful in the diagnostic evaluation of neuromuscular disorders 1–4 . As a result, the need for neuromuscular ultrasound training is also increasing.…”
Section: Introductionmentioning
confidence: 99%